Construction and Application of Interfacial Inorganic Nanostructures. Issue 7 (30th April 2020) - Wang, Rui; Wei, Yicheng; An, Li; Yang, Rui; Guo, Linchuan; Weng, Zheng; Da, Pengfei; Chen, Wenqing; Jin, Jing; Li, Jianyi; Xi, Pinxian
Abstract : Interfacial nanostructured materials have stimulated extensive interests in the research areas of green energy production and conversion due to their unique structures and performance. These interfacial crystalline structures with rich intrinsic defects, such as oxygen vacancies, adatoms, grain boundaries, and substitutional impurities, have led to unique activities in a variety of catalytic reactions. The rational design and engineering development of the interfaces provide an attractive way to optimize the catalytic performance and finally improve the efficiency of energy conversion and storage. Herein, a comprehensive overview of interfacial inorganic nanostructures and their electrocatalytic applications are summarized, and some future challenge and opportunity have also been proposed. Abstract : A comprehensive overview of interface focuses on the design, synthesis and electrocatalytic application of interfacial nanostructured materials.